Genome‐wide dissection of the maize ear genetic architecture using multiple populations. Issue 3 (30th December 2015) - Xiao, Yingjie; Tong, Hao; Yang, Xiaohong; Xu, Shizhong; Pan, Qingchun; Qiao, Feng; Raihan, Mohammad Sharif; Luo, Yun; Liu, Haijun; Zhang, Xuehai; Yang, Ning; Wang, Xiaqing; et al.
Summary: Improvement of grain yield is an essential long‐term goal of maize ( Zea mays ) breeding to meet continual and increasing food demands worldwide, but the genetic basis remains unclear. We used 10 different recombination inbred line (RIL) populations genotyped with high‐density markers and phenotyped in multiple environments to dissect the genetic architecture of maize ear traits. Three methods were used to map the quantitative trait loci (QTLs) affecting ear traits. We found 17–34 minor‐ or moderate‐effect loci that influence ear traits, with little epistasis and environmental interactions, totally accounting for 55.4–82% of the phenotypic variation. Four novel QTLs were validated and fine mapped using candidate gene association analysis, expression QTL analysis and heterogeneous inbred family validation. The combination of multiple different populations is a flexible and manageable way to collaboratively integrate widely available genetic resources, thereby boosting the statistical power of QTL discovery for important traits in agricultural crops, ultimately facilitating breeding programs.